Fecal Immunoglobulin A Against a Sporozoite Antigen at 12 Months Is Associated With Delayed Time to Subsequent Cryptosporidiosis in Urban Bangladesh: A Prospective Cohort Study. (25th May 2019) - Steiner, Kevin L; Kabir, Mamun; Priest, Jeffrey W; Hossain, Biplob; Gilchrist, Carol A; Cook, Heather; Ma, Jennie Z; Korpe, Poonum S; Ahmed, Tahmeed; Faruque, A S G; Haque, Rashidul; Petri, William A
Abstract: In this prospective cohort study of Bangladeshi children, greater fecal immunoglobulin A, but not plasma immunoglobulin G, directed against the Cryptosporidium sporozoite-expressed antigen Cp23 at 12 months of age was associated with delayed time to subsequent cryptosporidiosis. This finding suggests a protective role for mucosal antibody-mediated immunity in naturally exposed children.